2021
DOI: 10.3174/ajnr.a7350
|View full text |Cite
|
Sign up to set email alerts
|

Parent Artery Straightening after Flow-Diverter Stenting Improves the Odds of Aneurysm Occlusion

Abstract: BACKGROUND AND PURPOSE: Intracranial stents for the treatment of aneurysms can be responsible for parent artery straightening, a phenomenon with potential consequences for aneurysmal occlusion. We aimed to evaluate parent artery straightening following flow-diverter stent placement in patients with intracranial aneurysms and explored the association between parent artery straightening and subsequent aneurysm occlusion. MATERIALS AND METHODS:All patients treated with flow-diverter stents for anterior circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 13 ) It has also been reported that parent artery straightening is likely to be involved in higher occlusion rates in flow-diverter stents. 15 ) Specifically, it has been shown that a vessel angle of 20° or more likely indicates stable aneurysms, regardless of neck or aneurysm size. 16 ) In our case, the angle actually changed by more than 20° ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 13 ) It has also been reported that parent artery straightening is likely to be involved in higher occlusion rates in flow-diverter stents. 15 ) Specifically, it has been shown that a vessel angle of 20° or more likely indicates stable aneurysms, regardless of neck or aneurysm size. 16 ) In our case, the angle actually changed by more than 20° ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The SVB is a 48 self-expandable, braided construct composed of drawn filled tubes (DFTs) of platinum-filled nitinol, with the latter component contributing to elasticity and shape memory. 29 The mechanical properties and design of the stent facilitate visualization of the device, navigability, and controlled deployment. These characteristics are of great utility during the treatment of aneurysms located in small vessels, as some technical limitations are unique to this subset of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Michelozzi et al also reported a high occlusion rate of 92% occlusion in patients with at least 12 months of follow-up 13. These studies and others have suggested that complex interactions between mesh density of the stent, flow dynamics, geometrical modification (straightening) of the parent artery, changes in wall pulsatility, newer generation antiplatelet agents, and aneurysm neck coverage can affect occlusion rates 14 15. In general, however, aneurysm neck coverage cannot be manipulated by existing flow-diverting stents.…”
Section: Introductionmentioning
confidence: 96%